2017
DOI: 10.1016/j.fuel.2017.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Exhaust emissions of non-road mobile machine: Real-world and laboratory studies with diesel and HVO fuels

Abstract: Exhaust emissions emitted by a non-road mobile machine were studied chasing a tractor in real-world conditions and repeating the same transient tests with a similar engine on an engine dynamometer where additionally, nonroad steady state tests were carried out. The engines were equipped with an oxidation catalyst (DOC) and a selective catalytic reduction (SCR) system, and they were fuelled by fossil diesel fuel with ultra-low sulphur content and hydrotreated vegetable oil (HVO). By substituting diesel fuel wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…Environmental Protection Agency (EPA)'s recent emissions inventory data, off-road diesel equipment is estimated to be the third largest source for nitrogen oxides (NO x ) emissions and second largest source for particulate matter (PM) emissions, representing 14.5% and 24.3%, respectively, of total NO x and PM emissions from mobile sources (US EPA, 2013). A European study found that non-road machines made up about 31% and 42%, respectively, of total annual NO x and PM emissions from diesel power vehicles in Finland in 2014 (Pirjola et al, 2017). Wang et al (2016) found that in China off-road equipment emitted more PM 2.5 than all of the on-highway vehicles combined, and suggested that real world emissions and activity data for off-road equipment is "desperately needed".…”
Section: Introductionmentioning
confidence: 99%
“…Environmental Protection Agency (EPA)'s recent emissions inventory data, off-road diesel equipment is estimated to be the third largest source for nitrogen oxides (NO x ) emissions and second largest source for particulate matter (PM) emissions, representing 14.5% and 24.3%, respectively, of total NO x and PM emissions from mobile sources (US EPA, 2013). A European study found that non-road machines made up about 31% and 42%, respectively, of total annual NO x and PM emissions from diesel power vehicles in Finland in 2014 (Pirjola et al, 2017). Wang et al (2016) found that in China off-road equipment emitted more PM 2.5 than all of the on-highway vehicles combined, and suggested that real world emissions and activity data for off-road equipment is "desperately needed".…”
Section: Introductionmentioning
confidence: 99%
“…Tunnels and bridge are the components of a road with the greatest impact in terms of air emissions.Sustainability 2019, 11, 7218 2 of 14 mobile fonts. The adverse health and environmental effects of PM and trace gases have been confirmed by several studies [10][11][12].Numerous studies have focused on off-road equipment emissions inventories [5,7,8,[13][14][15]; however, the available data for comprehensive evaluations are still considerably more limited compared to the on-road mobiles sources. Few developed countries have published greenhouse gases (GHG) and non-GHG emission factor standards for non-road equipment.…”
mentioning
confidence: 99%
“…A noteworthy amount of PM 10 , often higher than that produced by other construction operations [21,22] are also released by the movement of the vehicles on dirty or unpaved and temporary roads in the worksites [23][24][25].In the literature, few studies deal with the real-world emissions from construction sites or with extensive evaluation on the emissions produced during the whole period of construction [26]. Some studies focused on data of exhaust emissions of the construction machineries [1,5,7,8]. Others investigated the influence of construction site emissions on local air quality [4,27,28] or calculated emission factors to assess emission inventories for all construction activities [21].Comprehensive studies that take into account all these objectives, and that consider various construction activities and processes and their duration, are scarce [1,6,29].…”
mentioning
confidence: 99%
See 2 more Smart Citations